If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 2 = 7y + -7 Reorder the terms: 2 + 4y = 7y + -7 Reorder the terms: 2 + 4y = -7 + 7y Solving 2 + 4y = -7 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 2 + 4y + -7y = -7 + 7y + -7y Combine like terms: 4y + -7y = -3y 2 + -3y = -7 + 7y + -7y Combine like terms: 7y + -7y = 0 2 + -3y = -7 + 0 2 + -3y = -7 Add '-2' to each side of the equation. 2 + -2 + -3y = -7 + -2 Combine like terms: 2 + -2 = 0 0 + -3y = -7 + -2 -3y = -7 + -2 Combine like terms: -7 + -2 = -9 -3y = -9 Divide each side by '-3'. y = 3 Simplifying y = 3
| 3-log(x)=0 | | -3(8y-4)=3(1-9y)+11 | | -22.9-a=21.5 | | 120-75= | | 3-ln(x)=0 | | 7(10w+10)+3w= | | 3m=m+32 | | 7x+43x+8= | | -5x-37=-11x+65 | | x+2(5)=10 | | 13x+1+9x+3+70=180 | | x+2(7)=10 | | -38-5n=-5(-7n-7)+7 | | x^3+x^2+64x+64=0 | | -76-5x=20+x | | A-7=8 | | -2b-5=-17 | | y=-(-5) | | x(3+6)=108 | | w-4=w-5-3 | | 28-(-5)= | | -3(4y-2)=-18 | | -8(-6a+-6)= | | 110=-4-5 | | pw+20s=x | | 7g+14-5g=18 | | 12x^6+324x^2-16x^9=0 | | -58.109=v+-47.736 | | -4-m=-41 | | 11x-7+3x-1+50=180 | | 22x-7-12x+2=20x-7-10x+17 | | -14-(-5)= |